Divorce of Early Marriage Mouples in Rantauprapat Religious Court - Rozali, M.; Dahris Siregar; Ritonga, Muhammad Ifdarsyam (SMART: Journal of Sharia, Traditon, and Modernity, 2025)
This article analysis the divorce case for teenage couples, the divorce process was carried out at the Religious Court of Rantauprapat City, North Sumatra. This article aims to analyze what are the factors of divorce for teenage couples and how is the process at the Rantauprapat Religious Court? The method used is qualitative to analyze the case, the case study research approach, the type of field research, data collection techniques through observation, interviews and documentation tracing. The research findings show that the factors of underage marriage in Rantauprapat are due to the economy, socio-cultural community and descent. While the reasons for divorce are because the teenage couple is not mature enough, lack of sense of responsibility, unfulfilled family income, neglected wife and children, husbands commit violence and cheating, this has an impact on household disharmony. Divorce for teenage couples is carried out by filing a lawsuit with the Rantauprapat Religious Court, the legal basis that is considered by the judge and the procedure has been in accordance with the applicable material and formal laws.